REKONSTRUKSI KEPRIBADIAN GURU PAI DI ERA ARTIFICIAL INTELLIGENCE: PENGUATAN PERAN GURU SEBAGAI MORAL ROLE MODEL DALAM PENDIDIKAN ISLAM - Guntur Maulana; Raiham Noor Azura; Rian Saepul Majid; Mursidin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid advancement of Artificial Intelligence has profoundly reshaped the educational sector, steering pedagogical processes toward increased digitalization, automation, and tailored learning experiences. Nevertheless, this shift has sparked significant apprehension regarding the potential erosion of students' ethical values, including integrity, accountability, and social consciousness. Within the framework of Islamic education, where character building is as vital as cognitive attainment, this challenge is particularly acute. This research seeks to examine the personality reconstruction of Islamic Religious Education teachers in the AI era, aiming to bolster their function as moral exemplars. Adopting a qualitative literature-based methodology, this study analyzes various scholarly works, journals, and international reports. The findings suggest that teachers confront not only technological hurdles but also deep-seated moral and personal challenges. Consequently, teacher personality reconstruction must prioritize the fusion of spiritual principles, digital fluency, and consistent ethical conduct across both physical and virtual environments. The study concludes that revitalizing the teacher’s role as a moral compass is imperative for preserving the foundational tenets of Islamic education in the digital age